Economic Valuation of Recreational Utilization of Chiang Khan Walking Street According to the Tourist Satisfaction Approach - Untong, Akarapong; Guntawongwan, Kansinee (Journal of Applied Economics and Management Strategy, 2023)
This article aims to assess the economic value of recreational utilization of Chiang Khan Walking Street. The tourists’ satisfaction approach (TSA) is applied to develop a model of factors describing visitor satisfaction, while the least square method with robust standard error is applied to estimate the coefficients from visitor interviewing data from the questionnaire of 297 samples. Results of the study found that walking or shopping activities in Chiang Khan Walking Street has the shadow price about 2,400 baht per person per trip and has the economic value of recreational utilization around 4.63 billion baht. While the activities to visit tourist attractions in the community have a shadow price of 2,100 baht per person per trip and have an economic value of recreational utilization of approximately 1.47 billion baht. Both activities have a combined economic value of recreational utilization of approximately 6.10 billion baht. The estimated shadow price reflects the value that visitors are willing to pay for the recreational use of both activities of Chiang Khan Walking Street. Therefore, the local authorities responsible for the Chiang Khan Walking Street can use the estimated shadow price to determine the fees for recreational use from visitors. This money can be used to take care of the development, safety, waste management, etc. that will support the use of Chiang Khan Walking Street leading towards sustainable tourism in the future.